2017
DOI: 10.5604/12321966.1232774
|View full text |Cite
|
Sign up to set email alerts
|

Motor assessment in Parkinson`s disease

Abstract: Parkinson's disease (PD) is one of most disabling disorders of the central nervous system. The motor symptoms of Parkinson's disease: shaking, rigidity, slowness of movement, postural instability and difficulty with walking and gait, are difficult to measure. When disease symptoms become more pronounced, the patient experiences difficulties with hand function and walking, and is prone to falls. Baseline motor impairment and cognitive impairment are probable predictors of more rapid motor decline and disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 9 publications
2
102
0
24
Order By: Relevance
“…17β‐HSD10 has the ability to promote neurodegenerative processes and apoptosis of neurons thereby playing an important role in neurodegenerative disorders (Oppermann et al., 1999; Yan et al., 1999). A role for 17β‐HSD10 is confirmed in Parkinson's disease (PD) (Tieu et al., 2004), which is a neurodegenerative disease manifested by the reduction in dopaminergic neurons in the substantia nigra resulting in motor symptoms as shaking, rigidity and postural instability, and walking problems (Opara, Małecki, Małecka, & Socha, 2017). Patients with PD have significantly down‐regulated the expression of 17β‐HSD10, resulting in reduced levels of the enzyme in dopaminergic neurons.…”
Section: β‐Hsd10‐related Diseasesmentioning
confidence: 99%
“…17β‐HSD10 has the ability to promote neurodegenerative processes and apoptosis of neurons thereby playing an important role in neurodegenerative disorders (Oppermann et al., 1999; Yan et al., 1999). A role for 17β‐HSD10 is confirmed in Parkinson's disease (PD) (Tieu et al., 2004), which is a neurodegenerative disease manifested by the reduction in dopaminergic neurons in the substantia nigra resulting in motor symptoms as shaking, rigidity and postural instability, and walking problems (Opara, Małecki, Małecka, & Socha, 2017). Patients with PD have significantly down‐regulated the expression of 17β‐HSD10, resulting in reduced levels of the enzyme in dopaminergic neurons.…”
Section: β‐Hsd10‐related Diseasesmentioning
confidence: 99%
“…Postural instability during level-ground walking, obstacle crossing, and ascending and descending stairs is widely described in the literature (6,7,(17)(18)(19)(20)(21). There is evidence that people with PD present impaired postural control during gait with an additional task (17,22,23); therefore, a complex motor activity from daily life, such as crossing an obstacle or negotiating stairs, may be hazardous for people with PD.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to mental symptoms, patients with PD display typical motor symptoms such as postural instability, muscle rigidity, static tremors and difficulty with walking and gait. 2 PD is a complex multifactor disease characterized by the extensive presence of α-synuclein-containing Lewy bodies in the substantia nigra (SN), in the pars compacta of which loss of dopaminergic neurons leads to reduced facilitation of voluntary movements. 3 Literature in the past decade has suggested that genetic factors might play an important role in the development of PD.…”
Section: Introductionmentioning
confidence: 99%